Educational Track, Networks and Labor Market Outcomes - David N. Margolis; Véronique Simonnet (Institute for the Study of Labor (IZA), 2003)
Does the educational track (technical or professional, as opposed to general) provide individuals with networks that are useful in the labor market? And how do these networks help? In this paper, we consider the effect of the educational track on the means by which individuals find employment, the time it takes to find their first stable job and their earnings once the school-to-work transition is well established. Using data in French school leavers from 1969-1992, we find that the educational track significantly influences the means by which jobs are found, favoring networks in particular, as well as having an independent direct effect on the speed of transition into the labor market and later earnings. We also find that the means by which a job was found significantly affects the time to first job and earnings, and in a way that offsets the direct effect of the educational track on our outcome variables.
Keywords: I28; J23; J21; J38; J31; 330; Educational system; educational track; networks; school-to-work transition; Absolventen; Berufseinstieg; Soziales Netzwerk; Arbeitsmarkt; Frankreich